Adverse outcomes associated with postoperative atrial arrhythmias after lung transplantation: A meta‐analysis and systematic review of the literature. Issue 4 (14th March 2017) - Waldron, Nathan H.; Klinger, Rebecca Y.; Hartwig, Matthew G.; Snyder, Laurie D.; Daubert, James P.; Mathew, Joseph P.
Abstract: Background: Postoperative atrial arrhythmias (AAs) are common after lung transplantation, but studies are mixed regarding their impact on outcomes. We therefore performed this systematic review and meta‐analysis to determine whether AAs after lung transplantation impede postoperative recovery. Methods: MEDLINE, EMBASE, CINAHL, and the Cochrane Register were searched to identify studies comparing outcomes in adult patients undergoing lung transplantation who experienced postoperative AAs in the immediate postoperative period vs those without postoperative AAs. Our primary outcome was perioperative mortality, and secondary outcomes were length of stay (LOS), postoperative complications, and mid‐term (1‐6 years) mortality. Results: Nine studies including 2653 patients were included in this analysis. Of this group, 791 (29.8%) had postoperative AAs. Patients with postoperative AAs had significantly higher perioperative (OR 2.70 [95% CI: 1.73‐4.19], P <.0001) mortality, longer hospital LOS (MD 8.29 [95% CI: 4.37‐12.21] days, P <.0001), more frequent requirement for tracheostomy (OR 4.67 [95% CI: 2.59‐8.44], P <.0001), and higher mid‐term mortality (OR 1.71 [95% CI: 1.28‐2.30], P =.0003). Conclusions: AAs after lung transplantation are frequent and associated with significantly higher mortality, longer hospital LOS, and requirement for tracheostomy. Given their impact on recovery, prophylactic strategies against AAs need to be developed.